4(2w-3)=2(3w+5)

Simple and best practice solution for 4(2w-3)=2(3w+5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(2w-3)=2(3w+5) equation:


Simplifying
4(2w + -3) = 2(3w + 5)

Reorder the terms:
4(-3 + 2w) = 2(3w + 5)
(-3 * 4 + 2w * 4) = 2(3w + 5)
(-12 + 8w) = 2(3w + 5)

Reorder the terms:
-12 + 8w = 2(5 + 3w)
-12 + 8w = (5 * 2 + 3w * 2)
-12 + 8w = (10 + 6w)

Solving
-12 + 8w = 10 + 6w

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '-6w' to each side of the equation.
-12 + 8w + -6w = 10 + 6w + -6w

Combine like terms: 8w + -6w = 2w
-12 + 2w = 10 + 6w + -6w

Combine like terms: 6w + -6w = 0
-12 + 2w = 10 + 0
-12 + 2w = 10

Add '12' to each side of the equation.
-12 + 12 + 2w = 10 + 12

Combine like terms: -12 + 12 = 0
0 + 2w = 10 + 12
2w = 10 + 12

Combine like terms: 10 + 12 = 22
2w = 22

Divide each side by '2'.
w = 11

Simplifying
w = 11

See similar equations:

| t^3+6t^2=25t+150 | | 3(X-2)=Xm+7 | | 5x+6=2x-2 | | 14=-5y+3(y-2) | | 18y=-20+19y | | -17-4k=3k+13-5k | | 0=-7r-3r | | 3(2x+5)=-37+22 | | 29=8+3x | | 25(x^2)-20x+4=0 | | 3g+9=4g | | 10-7k=-(8k-7) | | 8-9z=-5z | | 5-3(X-4)=11 | | -8=6(v-4)-8v | | -34+4p=-7(8+p) | | 7x-44=10-5x | | 0=7+5x^2-2x^3 | | 5+6h=-5+5h | | 4/5t+1=t+1/2 | | -3j-4j-1=-3j+7 | | 34=-8y+6(y+8) | | 16=p-5p | | -10-2n=-n | | 8n=7n-3 | | y=x^6-7x | | 9d=9+10d | | 4x^2-35x-414= | | 3w+15=48 | | 10B+8=68 | | -5(r+4)=-72 | | 10-7r=8-9r |

Equations solver categories